4th meeting of the EU research network EUROME: from the identification of genes and cellular networks in murine models of arthritis to novel therapeutic intervention strategies in rheumatoid arthritis, London, UK, 9 March 2004. - Ibrahim, S; Paleolog, E (2004)
Rheumatoid arthritis (RA) is a common human disease with a prevalence of about 1% in most parts of the world. At the time of symptom onset it is difficult to predict the severity of subsequent disease course. After 2 years joint erosions are seen in most patients, and most patients become clinically disabled within 20 years. A recent meeting at the Kennedy Institute of Rheumatology (Imperial College, London) brought together representatives from several European centres of excellence, to discuss research funded by the EU Framework 5 Quality of Life Programme. This research network combines gene and protein expression profiling with different animal models of RA to identify cells, genes and pathways contributing to arthritis initiation, progression and chronicity. The studies discussed highlight the reality that collaboration between different research groups is the basis of groundbreaking research and, it is hoped, eventual new therapies for RA.